2020
DOI: 10.1152/ajpgi.00021.2020
|View full text |Cite
|
Sign up to set email alerts
|

Impaired 25-hydroxylation of vitamin D in liver injury suppresses intestinal Paneth cell defensins, leading to gut dysbiosis and liver fibrogenesis

Abstract: Vitamin D deficiency is co-prevalent with various liver diseases including cirrhosis, while the underlying mechanism remains elusive. Vitamin D receptor (VDR) is abundantly expressed in the distal region of small intestine, where the Paneth cells are enriched, suggesting that vitamin D signaling may modulates the intestinal Paneth cells and their production of defensins to restrain microbiome growth in the small intestine. In this study we found that in carbon tetrachloride-induced liver injury, hepatic 25-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…Furthermore, knockdown of ATGs could restore YAP levels as well (Figure S3C). Endotoxin is known for its promotion of fibrotic stiffness [38,42], and here we noticed that additional treatment with LPS promoted nuclear localization of Yap in Pdx1-Kras mice, in agreement with increased pancreatic fibrosis and sprouting of ductal neoplasia (Figure 3A). The accumulation of Yap in KC mice treated with LPS was also related to increased phosphorylation of mTor and slowed turnover of p62/Sqstm1 and Lc3B, showing impairment of autophagic flux leading to Yap degradation (Figure 3A,B).…”
Section: Oral Administration Of Cationic Resin Leads To Mobilization ...supporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, knockdown of ATGs could restore YAP levels as well (Figure S3C). Endotoxin is known for its promotion of fibrotic stiffness [38,42], and here we noticed that additional treatment with LPS promoted nuclear localization of Yap in Pdx1-Kras mice, in agreement with increased pancreatic fibrosis and sprouting of ductal neoplasia (Figure 3A). The accumulation of Yap in KC mice treated with LPS was also related to increased phosphorylation of mTor and slowed turnover of p62/Sqstm1 and Lc3B, showing impairment of autophagic flux leading to Yap degradation (Figure 3A,B).…”
Section: Oral Administration Of Cationic Resin Leads To Mobilization ...supporting
confidence: 81%
“…Our previous work demonstrated that oral administration of cationic resin, such as cholestyramine, can sequester intestinal endotoxin (LPS), which consequently reduces systemic inflammation, improves insulin resistance, and relieves fatty liver and liver fibrosis [37,38]. Here, KC mice at 6 weeks of age were fed with or without cholestyramine in chow (3% w/w)-designated KC + CS and KC, respectively-for 14 consecutive weeks.…”
Section: Oral Administration Of Cationic Resin Attenuates Tumorigenes...mentioning
confidence: 99%
“… 100 Wu et al also reported that antibacterial peptide including defensins and lysozymes produced by Paneth cells were reduced in intestinal VDR conditional knockout mice. 101 After administrating a high-fat-diet plus vitamin D deficient feeding in mice, Paneth cell-specific alpha-defensins such as α-defensin5 (DEF5) and MMP7, were suppressed in the ileum, resulting in increased gut permeability, dysbiosis, and systemic inflammation. 102 A reduction in normal Paneth cells and an increase in abnormal Paneth cells (including disordered, depleted, and diffuse Paneth cells) were also observed in conditional VDR epithelial knockout mice.…”
Section: Vitamin D and Ibd Pathogenesismentioning
confidence: 99%
“…A recent study demonstrated the importance of vitamin D 25-hydroxylation in the small intestine in maintaining Paneth cell function [ 162 ]. Deficient hepatic 25-hydroxylation of vitamin D was demonstrated in carbon-tetrachloride-induced liver injury, resulting in the downregulation of defensins expressed in Paneth cells, gut dysbiosis, and endotoxemia [ 162 ]. Intestinal VDR knockout mice showed decreased Paneth cell defensins and lysozyme production, as well as worsening liver injury and fibrogenesis [ 162 ].…”
Section: Vitamin D Signaling and Gut Microbiota In Liver Diseasementioning
confidence: 99%